2014
DOI: 10.1590/s1516-635x2014000100012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different digestible lysine levels for male broilers during the period of 18 to 40 days of age

Abstract: A total of 1.500 male Cobb 500 broilers were used to determine the optimal digestible lysine level for 18 to 40-day-old broilers. The experimental period started when broilers were 18 days old and had an initial average weight of 737 ± 20 g. A completely randomized experimental design was applied, with five lysine levels, totaling five treatments with 10 replicates of 30 birds each. The experimental diets contained equal energy and protein levels, and 0.86, 0.95, 1.04, 1.13, and 1.22% digestible lysine. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Other amino acids were usually expressed as a percentage of lysine ( Emmert and Baker, 1997 ). Carlos et al (2014) indicated that the lower the digested lysine, the more the abdominal fat. The latter can be explained by the fact that an increase in the amino acid-lysine ratio will be oxidized and nitrogen will be excreted ( Lemme, 2003 ) or can be used as an expensive source of energy ( Storlie, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other amino acids were usually expressed as a percentage of lysine ( Emmert and Baker, 1997 ). Carlos et al (2014) indicated that the lower the digested lysine, the more the abdominal fat. The latter can be explained by the fact that an increase in the amino acid-lysine ratio will be oxidized and nitrogen will be excreted ( Lemme, 2003 ) or can be used as an expensive source of energy ( Storlie, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Melhores resultados de desempenho, como também rendimento de peito, foram obtidos com elevados níveis de metionina+cistina digestível na fase inicial ( ABDEL-MAKSOUD et al, 2010;YUAN et al, 2012), bem como na fase de crescimento (GOULART et al, 2011). A administração de diferentes teores de lisina na fase inicial ( ABDEL-MAKSOUD et al, 2010;TRINDADE NETO et al, 2011;OLIVEIRA et al, 2013) e na de crescimento (BERNAL et al, 2014;CARLOS et al, 2014), apontaram que os maiores valores do referido aminoácido estavam associados com o máximo desempenho e rendimento de peito, corroborando com os resultados deste estudo. Os resultados superiores de desempenho e rendimento de carcaça e de peito, nos tratamentos da programação linear e também maiores pesos absolutos de carcaça e suas partes, possivelmente são explicados pelo fato de a lisina ser considerada o principal aminoácido envolvido na síntese de proteína muscular e deposição nos tecidos (BERRI; BESNARD; RELANDEAU, 2008).…”
Section: Discussionunclassified